A Descriptive Study of Gestational Diabetes Mellitus in Yogyakarta - Indriani, Indriani; Hardyanti, Siti (Journal of Maternal and Child Health, 2022)
Background: Gestational Diabetes Mellitus (GDM) is a disorder of carbohydrate tolerance that increases blood sugar levels. It is first known during the second and third trimester of pregnancy. This study aims to determine the description of gestational diabetes mellitus (GDM) incidence in Sleman Yogyakarta in 2018. Subjects and Method: This research was observational descriptive with a retrospective approach. This study used secondary data wich written from medicalrecords blood sugar classifica-tion ≥105 gr/dL and fasting blood sugar ≥126 gr/dL. The population was 1023. The sample was 80 which was taken by using simple random sampling technique from January-December 2018 at Minggir Primary Health Center, Tempel I Primary Health Center and Mlati 1 Primary Health Center, Sleman, Yogyakarta. Results: The results of the study showed that from 80 pregnant women who examined their blood sugar levels, 47 subjects (58.8%) experienced DMG, 39 subjects (48.8%) aged ≥35 years, 50 subjects (62.5%) had preterm gestational age, 34 subjects (42.5%) had primary education (elementary/ junior high), 47 subjects (58.8%) did not work/housewives, 54 subjects (67.5%) were parity ≥2x, 38 subjects (47.5% ) were overweight, 47 subjects (58.8%) had GDM history, 47 subjects (58.8%) had hypertension in pregnancy, and 41 subjects (51.3%) had an incomplete Ante Natal Care (ANC) examination. Conclusion: It can be concluded that the incidence of GDM in Sleman is high, with characteristics of age at risk (≥35 years), history of previous illnesses and obesity.